2012
DOI: 10.1002/srin.201200019
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of FeO in EAF Steelmaking Slag by Blends of Metallurgical Coke and End‐of‐Life Tyre

Abstract: The reduction of FeO-containing slag by blends of metallurgical coke and end-of-life tyres (RT) have been investigated through experiments conducted in a laboratory-scale horizontal tube furnace. Composite pellets of EAF slag (47.1% FeO) with coke, RT, and blends of coke/RT (in four different proportions) were rapidly heated at 15508C under high purity argon gas and the off gas was continuously analyzed for CO and CO 2 using an online infrared (IR) gas analyzer. The extent of reduction after 10 min, level of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 8 publications
2
32
1
Order By: Relevance
“…The level of carburisation achieved (including pure HDPE) is sufficiently high to justify the observation of near perfect spherical shape. Dankwah et al (2012) observed that the time taken for complete melting of pellets decreased as the proportion of the polymer in the blend increased. No significant difference in the time for complete melting was observed in this investigation for the different blends used (melting time was 150 -250s).…”
Section: Content Of Carbon In the Re-duced Metalmentioning
confidence: 98%
See 2 more Smart Citations
“…The level of carburisation achieved (including pure HDPE) is sufficiently high to justify the observation of near perfect spherical shape. Dankwah et al (2012) observed that the time taken for complete melting of pellets decreased as the proportion of the polymer in the blend increased. No significant difference in the time for complete melting was observed in this investigation for the different blends used (melting time was 150 -250s).…”
Section: Content Of Carbon In the Re-duced Metalmentioning
confidence: 98%
“…Blending resulted in improved carburisation, as all the blends showed higher levels of carburisation than coke or HDPE. Dankwah et al(2012) attributed increased levels of carburisation to the presence of a hydrogen environment along with the fixed carbon content of a carbonaceous reductant. In the absence of hydrogen the metal is carburised mainly by reaction 2.…”
Section: Content Of Carbon In the Re-duced Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…For countries like Ghana where commercial quantities of iron ores are available, but without the relevant source of carbonaceous materials, waste polymers offer a readily available alternative to high grade metallurgical coke as reductant for iron making. In the metallurgical field, the use of postconsumer plastics as reductants or as a source of energy is currently gaining the attention of various researchers (Matsuda et al, 2006;Nishioka et al, 2007;Matsuda et al, 2008;Ueki et al, 2008;Dankwah et al, 2011;Kongkarat et al, 2011;Murakami et al, 2009;Murakami and Kasai, 2011;Dankwah et al, 2012;Dankwah et al, 2013;Dankwah and Koshy, 2014;Dankwah et al, 2015a;Dankwah et al, 2015b). However, most of the existing research in this area involves the use of thermoplastic polymers and or their blends with metallurgical coke, graphite, or biomass as reductants for the production of metallic iron from reagent grade iron oxides or electric arc furnace (EAF) slags containing iron oxide.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the existing research in this area involves the use of thermoplastic polymers and or their blends with metallurgical coke, graphite, or biomass as reductants for the production of metallic iron from reagent grade iron oxides or electric arc furnace (EAF) slags containing iron oxide. For thermosetting plastics, Dankwah et al, 2012, Mansuri et al, 2013, Rajarao et al, 2014a, Rajarao et al, 2014b, Nath et al, 2012and Dankwah and Baawuah, 2015 have used endof-life rubber tyres, waste compact discs, end-oflife melamine and waste bakelite as reductants or for carbon dissolution studies. Rajarao et al, (2014b) for instance studied the structural changes in the chars produced during the rapid pyrolysis of waste compact discs (CDs) in the temperature range 550-1550 °C.…”
Section: Introductionmentioning
confidence: 99%